2013
DOI: 10.3762/bjnano.4.26
|View full text |Cite
|
Sign up to set email alerts
|

A look underneath the SiO2/4H-SiC interface after N2O thermal treatments

Abstract: SummaryThe electrical compensation effect of the nitrogen incorporation at the SiO2/4H-SiC (p-type) interface after thermal treatments in ambient N2O is investigated employing both scanning spreading resistance microscopy (SSRM) and scanning capacitance microscopy (SCM). SSRM measurements on p-type 4H-SiC areas selectively exposed to N2O at 1150 °C showed an increased resistance compared to the unexposed ones; this indicates the incorporation of electrically active nitrogen-related donors, which compensate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…This effect has been quantified by Fiorenza et al [51], by means of cross sectional scanning capacitance microscopy (SCM) measurements on the SiO 2 /4H-SiC interface. In particular, SCM in cross sections showed that the faceted 4H-SiC surface morphology incorporates a larger nitrogen amount compared to the basal planes, because it exposes different ratios between (0001) and (11−20) planes [47]. Other studies based on transmission electron microscopy (TEM) [52,53] and X-ray photoemission spectroscopy (XPS) [49] demonstrated that nitrogen is incorporated within a couple of 4H-SiC crystalline monolayers.…”
Section: Effects Of Counter Doping and Interface Stressmentioning
confidence: 97%
See 2 more Smart Citations
“…This effect has been quantified by Fiorenza et al [51], by means of cross sectional scanning capacitance microscopy (SCM) measurements on the SiO 2 /4H-SiC interface. In particular, SCM in cross sections showed that the faceted 4H-SiC surface morphology incorporates a larger nitrogen amount compared to the basal planes, because it exposes different ratios between (0001) and (11−20) planes [47]. Other studies based on transmission electron microscopy (TEM) [52,53] and X-ray photoemission spectroscopy (XPS) [49] demonstrated that nitrogen is incorporated within a couple of 4H-SiC crystalline monolayers.…”
Section: Effects Of Counter Doping and Interface Stressmentioning
confidence: 97%
“…Fabrication details can be found in Reference [55]. As can be seen, the number of free carriers in the nitridated sample is increased by more than one order of magnitude in a region about 10 nm wide from the SiO2/4H-SiC interface [47,51]. Thus, it can be concluded that the nitridation process modifies only a small fraction of the 4H-SiC crystal (one-two monolayers) but it increases the free carrier concentration in the MOSFET inversion region, effectively reducing the channel resistivity.…”
Section: Effects Of Counter Doping and Interface Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, two-dimensional (2D) carrier profiling techniques based on atomic force microscopy, such as scanning capacitance microscopy (SCM) and scanning spreading resistance microscopy (SSRM), have been also explored to evaluate the electrically active profiles in ion-implanted 4H-SiC [ 14 ]. In particular, the SCM technique, based on local differential capacitance (dC/dV) measurements with a sliding metal tip, is very powerful for the delineation of the electrical junction position in semiconductor devices, by exploiting the sensitivity to the doping type of the dC/dV phase signal [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although many methods have been adopted to improve the surface roughness, such as using a protective layer of a graphitic cap, there still exists controversy about the influence of SiC/SiO 2 interface morphology after the postimplantation annealing on the interface state density and channel mobility. Fiorenza [3] , recently reported that the carbon cap used to protect SiC surface during 1650 C high temperature annealing results in an increased interface state density (D it ) and a decreased channel mobility compared to the devices without carbon cap. They attributed the increased D it to the different areal percentage exposing different basal planes before and after carbonization [4] .…”
Section: Introductionmentioning
confidence: 99%